Labor supply after transition: evidence from the Czech Republic - Alena Bičáková; Jiri Slacalek; Michal Slavík (European Central Bank (ECB), 2008)
We extend the scarce evidence on labor supply in post-transition countries by estimating the wage elasticity of labor force participation in the Czech Republic. Using the household income survey data of 2002, we find that a one-percent rise in the gross wage increases the probability of working by 0.16 and 0.02 percentage points for women and men, respectively. Taking into account the tax and benefit system, these semi-elasticities fall to 0.06 for women and 0.01 for men. We interpret the difference between the estimates from the two specifications as a summary measure of the welfare system disincentives. The estimated wage elasticities lie at the lower end of the range of values reported for mature market economies. This finding is consistent with the stylized fact that the labor supply in countries with high labor force participation rates, such as in the Czech Republic, tends to be less sensitive to wages.
Keywords: J22; J31; P30; 330; Labor supply; Transition; welfare system; Arbeitsangebot; Erwerbstätigkeit; Elastizität; Schätzung; Tschechien